Pengaruh Early Warning Score terhadap Keselamatan Pasien - Masela, Victor Carlos; Kosasih, Cecep Eli; Emaliyawati, Etika (Journal of Telenursing (JOTING), 2023)
This study aims to identify the application of the Early Warning Score (EWS) system to patient safety. The method used is Literature Review. Article searches have been carried out comprehensively using the Pubmed and Google Scholar databases. Search for articles with the keywords Early Warning Score, Emergency, Patient Safety. The research results show that safety increases from early detection using EWS. EWS is very influential in improving patient safety. EWS is a scoring system that is simple, practical, easy to use and does not increase the workload of nurses. The influence of nurse competency using EWS can improve patient safety because it makes nurses compete to improve knowledge and skills, nurse communication, decision making, and collaboration with other health workers. In conclusion, the application of the Early Warning Score is very influential in supporting patient safety, where the Early Warning Score can detect patient deterioration early so that nurses are able to carry out further nursing actions. Apart from that, nurses' understanding and good nursing skills can support patient safety. Keywords: Emergency, Patient safety, Early Detection Score